The macroeconomics of the global technology economy - Rubin, Howard A. (FT Press Delivers digital shorts, 2012)
In 2010, global technology spending exceeded $4.2 trillion, equivalent to the world's fourth largest economy--and its growth rate is substantially outstripping GDP growth in advanced economies. Virtually overnight, a massive "global technology economy" has emerged--and it's gained far more influence than most decision-makers recognize. Understanding this economy is now crucial for every investor, executive, strategist, and policymaker. In The Macroeconomics of the Global Technology Economy , world-renowned expert Dr. Howard A. Rubin illuminates it as never before. Rubin helps you recognize, map, and understand how technology investments interact with value creation, and use this knowledge to optimize your own technology investments, whether you're operating on a corporate, national, or global level. In a world that's changing at breakneck speed, he helps you understand the role of technology in driving that change--drilling down to variables ranging from availability of IT skills and high-speed Internet connections to the growth of computer power. Along the way, he also discusses sectors pioneering especially intense IT usage, notably financial services, where 92% of business costs now relate to data. Rubin concludes with an overview of the navigational disciplines and iterative, real-time processes that companies will need to optimize performance and competitiveness in a world that's becoming increasingly IT and data-centric.